Perbedaan Hasil Belajar Siswa Menggunakan Mind Map Dan Tanpa Menggunakan Mind Map Materi Sistem Pencernaan Manusia - Rafeah Husni (Bioedunis Journal, 2022)
This study aims to determine the differences in learning outcomes of students who were taught using and not using Mind Map technique in topic of human digestive systemin in XI Grade of Science Program SMA Negeri 1 Panyabungan. Kind of this research is an experimen research. The population of the research is all of the student in XI Grade of Science Program SMA N 1 Panyabungan which included into 4 classes with total 154 students. Samples in this study were 2 classes consisting of 74 students with a cluster random sampling technique. No difference in learning outcomesin both these studies clas of research is evidenced through hypothesis testing using t-test with confidence level α = 0.05, where tcount ˂ ttable (0,54 ˂ 1.67), which means that the research in H0 be accepted and Ha is rejected. Concluded that there was no statistical difference in which class Mind Map (1 X = 66,40 ; SD = 12,48) and class without Mind Map (2 X = 64,95 ; SD = 10,35) in topic of human digestive system in XI IPA N 1 Panyabungan High School.